Regional dialogue on renewed policy action for the poorest and hungry in South Asia - Shastry, Paromita; Ahmed, Akhter; Pandya-Lorch, Rajul; Sharma, Manohar; Fritschel, Heidi (Asian Development Bank, 2008)
Despite rapid income growth, South Asia has lagged behind the rest of Asia in reducing poverty and hunger. South Asia accounts for more than two-fifths of the world's poor, and although the region seems on track to meet the first Millennium Development Goal (MDG) of halving poverty and hunger by 2015, it faces challenges in achieving that goal. The International Food Policy Research Institute (IFPRI), with support from the Asian Development Bank (ADB) and the International Fund for Agricultural Development (IFAD), held a regional dialogue of policymakers and researchers, called "Renewed Policy Action for the Poorest and Hungry in South Asia," in New Delhi on December 2, 2008. Following up on the international conference "Taking Action for the World's Poor and Hungry People" held by IFPRI in 2007 in Beijing, participants in this regional dialogue discussed two key issues: (1) how to secure inclusive income growth and (2) how to enhance the human capabilities of the poorest people. Participants shared experiences and debated how to replicate and scale up successful experiments as well as how to move from research to action and from policy to implementation.